The Innovation and Strategies for Developing Non-Test Instruments and Observational Interviews in Student Competency Assessment - saputri, Endang; Astuti, Widia; Hidayat, Rahmat (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The development of non-test instruments such as interviews and observations in student competency assessments is becoming increasingly important amidst the demands of the Independent Curriculum which emphasizes holistic assessment. This instrument allows the measurement of affective and psychomotor aspects that are not covered by conventional tests. This article aims to examine innovations and strategies for developing non-test instruments based on the results of research in the last five years (2020–2025). The method used is a systematic literature review with a descriptive qualitative approach. Data were collected from five selected relevant articles, analyzed thematically to identify patterns, strategies, and research gaps. The results of the study indicate that the use of structured and valid interviews and observations can increase the accuracy of student competency assessments, especially in the affective and psychomotor domains. In addition, it was found that teacher training and instrument digitalization were important factors in the successful implementation of non-test assessments. These findings contribute to the theory of authentic assessment and expand the practice of context-based assessment. The implications of this study encourage the need for the development of more adaptive instruments and the integration of technology in the implementation of non-test assessments in schools. Further research is recommended to explore the teacher training model and psychometric validation of the instrument in more depth.